Dinamika Konsep Keamanan-Pertahanan Ukraina Pasca Invasi Rusia Sebagai Pembelajaran Bagi Indonesia - Defrida Suzana Lukuaka (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
The Russia-Ukraine War serves as one of the most recent examples of modern warfare where war no longer remains at a conventional level but has shifted to hybrid warfare. Ukraine, as a country that gained independence only in 1991, has quickly been able to counterbalance Russia despite overall still facing several issues, one of which is the hindrance of Ukraine's own military reform. However, Ukraine has gradually been able to make significant changes in its security and defense during the Russian invasion. These changes range from defense bureaucracy to soldiers on the battlefield. Ukraine's experience can serve as a lesson for Indonesia in terms of military reform, defense flexibility in facing the dynamics of modern warfare, and the ability to enhance cooperation in the regional area as a "Based Shield." This article uses qualitative research methods through a literature study approach. The research found that strategically, Indonesia can learn from Ukraine's Security-Defense policies without abandoning Indonesia's maritime defense characteristics.